MASA DEPAN CREATIVE INDUSTRY INDONESIA: CATATAN KRITIS STRATEGI KEBUDAYAAN - Sutanto, M. Himawan (Jurnal Bestari, 2009)
Global crisis has forced many countries thinking how to survive to face it. There are many strategic ways to maintain their financial crisis, from doing recovery until recontrolling the industries. In Indonesia, creative industry is one of the great sector in our gross domestic product. Since 2004 to 2008, there was a positive trend. So, there were many opportunities for this sector. In addition, movie is the one of this sub-sector. If the goverment has a good and great strategy in empower the culture, this sector can support our gross domestic product. Thus, it can become a lucrative sector in the future.